ChemInform Abstract: Synthesis of Dibenzophosphole Oxides via Palladium‐Catalyzed Intramolecular Direct Arylation Reactions of ortho‐Halodiarylphosphine Oxides. Issue 39 (23rd September 2014) - Cui, Yuming; Fu, Lingzi; Cao, Jian; Deng, Yuan; Jiang, Jianxiong
Abstract A facile protocol is developed for the synthesis of dibenzophosphole oxides through palladium‐catalyzed direct arylation reaction of readily available ortho‐halodiarylphosphine oxides.